Orthopedic Patients and Use of Complementary and Alternative Medicine in Port Harcourt, Nigeria - Aaron, Friday E.; Ijah, Rex Friday Ogoronte Alderton; Harcourt, Somiari L.; Achor, Mike (British Journal of Healthcare and Medical Research, 2024)
Background: The use of Complementary and Alternative Medicine (CAM) is a global phenomenon with increasing popularity. This study evaluated the use of complementary and alternative medicine (CAM) among orthopaedic patients for proportion, types and reasons for usage in Port Harcourt, Nigeria in the last quarter of the year 2022. Materials and Methods: A descriptive and cross-sectional study was carried out among orthopedic patients in two Teaching Hospitals, using interviewer-administered questionnaire. Statistical analysis was done using IBM SPSS (Version.23.0). Results: The respondents’ mean age was 36.3±6.30 years. There were 245 (51%) males and 240 (49%) females, and more than half had at least a secondary education. Sixty percent of Orthopedic patients actively used CAM products. The most commonly used in decreasing order of frequency were prayers in religious houses (n = 290, 60%), honey and its products (n = 199, 41%), ginger extract (n = 192, 39%), traditional/oriental massage (n = 184, 38%), garlic extract (n = 170, 35%), and herbal medications (n = 170, 35%). The most common reasons for usage of CAM were lack of money/modern medicine expenses (n = 315, 65%), ineffectiveness of modern medicine 242(50%); to promote hospital effort for quick relief (n = 331, 68%); and to promote and maintain health (334, 69%). Conclusion: Type of CAM products in “current” use in order of decreasing frequency, were religious mind/body interventions, biological based therapy, and traditional/oriental massage. Multiple reasons were given for CAM usage. Formal public enlightenment and regulation bby government agencies is highly recommended.